PENGEMBANGAN MEDIA PEMBELAJARAN IPEX (INTELLIGENT PROPERTY EXCELLENT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Lapananda, Eva Rivana; Abdullah, Gamar; Arif, Rifda Mardian; Katili, Sukri; Panai, Abdul Haris (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study is to develop IPEX learning media that meets the criteria of feasibility, practicality, and effectiveness in science learning to improve student learning outcomes in ecosystem material in grade IV of SDN 6 Kabila. This study is a development research using the ADDIE development research model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility of IPEX media was tested through validation by a team of experts. The validation results showed that this media obtained an average percentage of 95.14%, which was categorized as very feasible for use by teachers and students in elementary schools. To test the practicality, the researcher used the teacher observation sheet, which showed a total score of 39 out of a maximum score of 40, with an average percentage of practicality reaching 97.5%, falling into the very practical category. In terms of effectiveness, the application of media in class IV of SDN 6 Kabila was measured through pretest and posttest. As a result, the average pretest score of 36.5% increased to 83% in the posttest, with a difference in increase of 46.5%. The level of effectiveness of IPEX media based on calculations reached 72.41%, indicating that IPEX media is included in the effective category. Based on these results, IPEX media has proven to be effective in improving student learning outcomes and is suitable for use in learning in elementary schools.